2014
DOI: 10.1371/journal.pone.0103588
|View full text |Cite
|
Sign up to set email alerts
|

Total Aortic Arch Replacement: Superior Ventriculo-Arterial Coupling with Decellularized Allografts Compared with Conventional Prostheses

Abstract: BackgroundTo date, no experimental or clinical study provides detailed analysis of vascular impedance changes after total aortic arch replacement. This study investigated ventriculoarterial coupling and vascular impedance after replacement of the aortic arch with conventional prostheses vs. decellularized allografts.MethodsAfter preparing decellularized aortic arch allografts, their mechanical, histological and biochemical properties were evaluated and compared to native aortic arches and conventional prosthes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Other authors published similar histological and mechanical findings to ours, examining the effects of the different decellularization methodologies [1, 6]. SDS/NaN 3 (protocol 2) and Triton X-100/sodium deoxycholate/nuclease (protocol 4) treatment were also effective in cell elimination, while mechanical properties showed no remarkable alteration, compared with untreated samples [1, 6].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Other authors published similar histological and mechanical findings to ours, examining the effects of the different decellularization methodologies [1, 6]. SDS/NaN 3 (protocol 2) and Triton X-100/sodium deoxycholate/nuclease (protocol 4) treatment were also effective in cell elimination, while mechanical properties showed no remarkable alteration, compared with untreated samples [1, 6].…”
Section: Discussionsupporting
confidence: 77%
“…SDS/NaN 3 (protocol 2) and Triton X-100/sodium deoxycholate/nuclease (protocol 4) treatment were also effective in cell elimination, while mechanical properties showed no remarkable alteration, compared with untreated samples [1, 6]. In addition, Weymann et al [6] confirmed no significant change in collagen and elastin content using the Biocolor assay, together with significantly reduced DNA content after decellularization using SDS and NaN 3 in PBS with spectrophotometric DNA quantification (protocol 2), supporting superb applicability of this method. Further research with alternative methodology is warranted to better understand the feasibility of this technique in routine use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial elastance (Ea) was calculated as LVESP/SV. Ventriculoarterial coupling (VAC) was described by the quotient of Ea and ESPVR (44).…”
Section: Methodsmentioning
confidence: 99%
“…The slope of the enddiastolic pressure-volume relationship (EDPVR) was calculated as a reliable index of LV stiffness. Additionally, arterial elastance (Ea) was calculated, and ventriculo-arterial coupling was described by the quotient of ESPVR and Ea (24).…”
Section: Sham-operated and Bddmentioning
confidence: 99%